E-marketing development for brown sugar cane product - Nur Laely; Bothy Dewandaru; Sudjiono Sudjiono; Lisrohmatin Lisrohmatin; Arnella I Nowhaf Tiko (Community Empowerment, 2022)
The Covid-19 pandemic has significantly impacted the economy, particularly MSMEs. The Production of Brown Sugar Cane, Ds. Mangunrejo Ngadiluwih, is one of the MSMEs that is impacted since they still utilize old marketing techniques and are less innovative. This program intends to encourage MSMEs engaged in the production of brown sugar cane to become knowledgeable and skilled in e-marketing so they can compete effectively and make the most money possible during the pandemic. Training is the method employed in this activity. The outcomes of this program include expanding MSME players' knowledge of and skills in using digital technologies to boost marketing productivity and expand the marketing reach.